Gambaran Tingkat Kepuasan Pasien Tentang Pelayanan Di Instalasi Gawat Darurat Rumah Sakit Umum Daerah Sukoharjo - Wiyono, Hagus, Sulastri S.Kep., M.Kes (2016)
Emergency Room (ER) is one of the main lines as the influx of patients, then do triage and given help. Handling emergency patients in the emergency department is no philosophy which is Life Saving Time saving means that all actions taken during emergency conditions must be truly effective and efficient. This is because the patient may have lost their lives in a matter of minutes. ER nurse job characteristics cause nurses are often more concerned with the process of saving the patient than the interaction with patients and their families, allowing the perception of the patient or the patient's family to be less good nursing care. This study aims to determine patient satisfaction level overview of the services in the Emergency Room at the General Hospital of Sukoharjo, Sukoharjo. This research is descriptive. Sample studies are visitor IGD Sukoharjo District Hospital that as many as 100 respondents with accidental sampling technique. Collecting data using questionnaires analyzed using analysis of importance performance analysis (IPA) and the test gap / gap. The result of the study are (1) the level of reality patients are mostly satisfied, (2) the level of patient expectations are mostly very satisfied, (3) the dimension of service that must be upgraded in service improvement in ER Hospital Sukoharjo are nurses provide information before the service, patient greeting with friendly, nurses heard the complaints of patients, nurses are patient in outreach, nurses are patient in providing services, nurse-groomed and attractive in outreach. The conclusion of this study were the level of patient satisfaction with care nurses in ER Hospital Sukoharjo that the dimension of responsiveness (responsiveness), assurance (assurance), tangible (tangible), and empathy (empathy), while the dimension of reliability (reliability) is very satisfied. Keywords: the level of satisfaction, patients, the ER